Ictiofauna del arroyo La Choza, cuenca del río de la Reconquista (Buenos Aires, Argentina) - Colautti, Darío César (2009)
As part of the project “Global changes in river systems: effects on biodiversity, food web and system functioning” fish community of La Choza stream was initially estimated and then compared with existing literature of pampean plain streams. From May 2007 to June 2008 five fish samples were taken in two sampling stations. Species occurrence, diversity (H´) and evenness (J) were estimated. Similarity in species composition with ten pampean streams was performed using cluster analysis. 2935 specimens collected represented 23 species (13 permanent, 7 semi-permanent and 3 occasional) and 10 families. Characiformes and Siluriformes were dominant. Although species richness was similar in both sites, diversity index was higher at downstream station. Differences between stations could be related to channel shape, bottom profile and sediment type. The cluster analysis showed that position of the water course within the basin and pollution are both important in the ichthyofauna composition determination.